A dynamic instrumentation tool for obtaining software logs. (November 2020) - Zhou, Hongchen; Li, Jing
Abstract: Compared with the software analysis based on source code, log based software analysis technology has gradually emerged in recent years, but it is not easy to obtain the log of software. To automatically obtain enough information on the software log, this paper proposes a dynamic instrumentation tool, it can dynamically instrument a software implemented in Java language, and get the log finally. This tool does not require users to be familiar with the software, and the instrumentation process will not cause an intrusive impact on the source code. It is a general-purpose automatic dynamic instrumentation tool.